2021
DOI: 10.2478/jas-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and Accompanying Fauna of Red Mason Bee Osmia rufa L. (syn. Osmia bicornis L.) in Areas with Different Levels of Urbanization

Abstract: An increasing number of studies show that urbanized areas are habitats of high biological value and ecological significance. Most bee species live in areas altered by man, either in cities - fragmented urban habitats - or in large rural monocultures. Our research is based on three-year observations of population development of the solitary bee Osmia rufa L. in three habitat types: city, suburbs and villages. We compared reproductive parameters and diversity of accompanying nest fauna. Population growth rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(57 reference statements)
0
4
1
Order By: Relevance
“…In urban habitats and berry plantations bees occupied a similar percentage of nesting tubes, over 50%, while, in orchards, they occupied more than 60% of nesting tubes (Table 1). These were low results compared to studies on the urbanization gradient, where the percentage of settlements in urban and agricultural habitats was over 90% [41]. The percentage of occupied nests influenced the population growth, which was much higher in orchards (3.97) than in berry plantations or urban habitats (3.60 and 3.09, respectively).…”
Section: Bee Population Grow Rate In Urban Orchards and Berry-plant H...contrasting
confidence: 63%
See 2 more Smart Citations
“…In urban habitats and berry plantations bees occupied a similar percentage of nesting tubes, over 50%, while, in orchards, they occupied more than 60% of nesting tubes (Table 1). These were low results compared to studies on the urbanization gradient, where the percentage of settlements in urban and agricultural habitats was over 90% [41]. The percentage of occupied nests influenced the population growth, which was much higher in orchards (3.97) than in berry plantations or urban habitats (3.60 and 3.09, respectively).…”
Section: Bee Population Grow Rate In Urban Orchards and Berry-plant H...contrasting
confidence: 63%
“…Each tube was cut open with a scalpel and the number of breeding cells in which there were cocoons, dead larvae, and pupae, or parasites was recorded. In this study, we determined the parameters of the population, which were used in previous studies [41]: a. Percent of tubes occupied by bees in relation to all tubes in the nest.…”
Section: Nest Analysis and Bees' Reproductive Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors determined that in comparison with one-year-old tubes, in the two-yearold cane tubes there are more than ten times less healthy cocoons and three times more injured or destroyed cocoons, with a wider diversity of parasites [33]. Additionally, it was previously reported that continuous breeding in the same place for more than ten years means significantly higher numbers and diversity of brood parasites in nests [34,35]. Our results showed the lowest determined bees SL was at L3, which was 13.80% in total, while in a similar environment of L2, it was 28.05%.…”
Section: Discussionmentioning
confidence: 99%
“…IPA infection intensity of managed and wild bees varies naturally throughout the season 12 , 13 , 34  and is also affected by available floral resources 38 44 , climatic conditions 45 48 , habitat quality 44 , urbanisation intensity 49 51 , density of managed bees 44 , 52 and interacting environmental factors 53 55 . The specific and temporary deployment of large numbers of managed honey bees, bumble bees or solitary bees for crop pollination may therefore represent a threat to native wild bee populations, through competition for limited floral resources and nest sites 9 , 56 , 57 , and through IPA transmission in overlapping foraging networks 8 , 58 63 or direct contact between bees or their faeces.…”
Section: Introductionmentioning
confidence: 99%